GRAVES'S DISEASE IS ASSOCIATED WITH PANCYTOPENIA AND SPLENOMEGALY RESPONSE TO STEROID THERAPY - Imam, Motwakil Imam Awadelkareim (International Journal of Pharma and Bio Sciences, 2026)
Graves's disease is an autoimmune disease characterized by hyperthyroidism due to circulating autoantibodies. Thyroidstimulating immunoglobulins (TSIs) bind to and activate thyroid-tropin receptors, causing the thyroid gland to enlarge and the thyroid follicles to produce more thyroid hormone. In certain individuals, Graves's disease may be a component of more widespread autoimmune conditions that affect several organs (such as polyglandular autoimmune syndromes). Pernicious anemia, vitiligo, diabetes mellitus type 1, systemic sclerosis, myasthenia gravis, Sjogren syndrome, rheumatoid arthritis, and systemic lupus erythematosus are all linked to Graves's disease. A few instances of this uncommon and little-known "entity" have been reported. Herein, I describe the association of Graves's disease associated with pancytopenia and splenomegaly response to steroid therapy. We suggest that such an association has been very rarely reported. Case study: A 55-year-old Sudanese male presented to us at ELmek Nimer University Hospital complaining of generalized fatigability with symptoms and signs of Graves ' disease. He also looked pale on the abdominal examination; there was a huge splenomegaly, a complete blood count showed features of pancytopenia, and all components of blood and cells were low. We diagnosed him with autoimmune thyroid disease associated with splenomegaly and started treatment with steroids, which showed improvement clinically and in the laboratory. In Graves' disease, four well-known thyroid antigens are known to be targets of B and T lymphocyte-mediated autoimmunity: thyroglobulin, thyroid peroxidase, sodiumiodide symporter, and thyrotropin receptor. Nonetheless, the thyrotropin receptor itself is the main autoantigen of Graves's disease, and it also results in hyperthyroidism. The immune responses specific to the thyroid antigen mediated by antibodies and cells are well-defined in this disease. The development of hyperthyroidism in healthy subjects by transfer of thyrotropin receptor antibodies in serum from patients with Graves's disease and the passive transfer of thyrotropin receptor antibodies to the fetus in pregnant women are direct indications of an autoimmune disorder mediated by autoantibodies. We recommend that steroid 'therapy' should be considered as one of the modalities in the management of pancytopenia, splenomegaly associated with Graves's disease, in combination with ant-thyroid treatment.